Quantitative structure-cytotoxic activity relationship of phenylthiourea derivatives from ChemBL database on sirtuin-1 receptor by in silico - Nasyanka, Anindi Lupita (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2019)
Rational drug design becomes a necessity amid the development of drugs that are inefficient and time-consuming. Hansch's QSAR helps reduce these shortcomings supported by the role of biocomputation. Some of the roles of biocomputation that can be used include in silico testing and the availability of databases for new drug-receptor and ligand candidates. This study aims to determine the QSAR through the search for the best equations analyzed by ANOVA statistics between cytotoxic activity in silico (Log 1/c) anticancer compounds derived from phenylthiourea stored in the ChemBL database with lipophilic parameters (ALPP and AlogP) , electronic (ACDpKa), and its sterics (PMW). The best equation is obtained Log 1/c = -46,194 - 0,152 PMW- 3,769 ALogP - 1,336 ACDpKa with a value of N = 28; F = 20,866; r = 0,850;Â  P = 0,000; SE = 5.82160. In the future, this equation can be used to find other new phenylthiourea derivatives that have better cytotoxic activity.